Anti-complementary Activity of Several Dimethyltin Carboxylates and Dimethyltin Carboxylates and Dimethyltin Dichloride Complexes with Various Donor Ligands - F. Khuzaie, Rula; J. Rashan, Luay; A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
The anti-complementary activities have been evaluated in vitro (using a test that detects complement proteins inhibition) for several dimethyltin carboxylates of the general formula Me2SnX2 [X = 1/2O2(CO)2 (oxalate), 1/2O2(CO)2CH2 (malonate), 1/2O2(CO)2CH=CH (maleate), 1/2O2(CO)2 C—CH2CH2CH2 (cyclobutyl dicarboxylate), O(CO)C6H11 (cyclobutyl carboxylate) and O(CO)CMe3 (pivolate)] and dimethyltin dichloride complexes of the general formula Me2SnCl2.L [L = 8-hydroxy quinoline (L1), 8-hydroxy quinoline-N-oxide (L2), 2,6-diaminopyridine (L3), cyclohexyl amine (L4), (1R, 2R)-1,2-cyclohexane diamine (L5), 3,5-dimethylpyrazole (L6), harmaline (L7) and harmine (L8)]. The results obtained have been compared with those of the three known anticancer drugs (cisplatin, carboplatin and oxaliplatin) and with that of the starting material Me2SnCI2. Three of the tin compounds displayed remarkable anti-complementary activities (IC50≤ 0.1 μg mL-1) which are almost similar to those of the drugs and tenfolds better than that of Me2SnCl2 (IC50 = 1.0 μg mL -1).